1999
DOI: 10.3923/pjbs.1999.767.771
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Relationship Between Morpho-phenological Traits and Grain Yield in Winter and Facultative Barley under Stress Environments

Abstract: Variability and relationship among different morpho-phenological traits for twenty four lines/varieties in each of the two winter and facultative barley trials were studied at two locations (Tel. Hadya and Breda) in northern Syria. A significant variation was observed in barley lines for grain yield, plant height, days to heading and maturity, grain filling period and growth period. Since the winter during 1994-95 was mild at the both locations and drought and high temperatures were major stresses, most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…The positive and significant correlation coefficients (r-values) between grain yield and the yield components such as plant height, spike length, kernel number per spike, kernel weight per spike, spike number per m 2 and harvest index were 0.191**, 0.265**, 0.406**, 0.247**, 0.361**, and 0.474**, respectively. Similar results for grain yield and plant height in barley were reported by other studies (Bhutta et al, 2005;Kisana et al, 1999;Samarrai et al, 1987). Akdeniz et al (2004) observed positive and significant correlations between grain yield and yield compo-The indirect effects of yield components on grain yield on one another were generally positive with some exceptions.…”
Section: Resultssupporting
confidence: 90%
“…The positive and significant correlation coefficients (r-values) between grain yield and the yield components such as plant height, spike length, kernel number per spike, kernel weight per spike, spike number per m 2 and harvest index were 0.191**, 0.265**, 0.406**, 0.247**, 0.361**, and 0.474**, respectively. Similar results for grain yield and plant height in barley were reported by other studies (Bhutta et al, 2005;Kisana et al, 1999;Samarrai et al, 1987). Akdeniz et al (2004) observed positive and significant correlations between grain yield and yield compo-The indirect effects of yield components on grain yield on one another were generally positive with some exceptions.…”
Section: Resultssupporting
confidence: 90%
“…Ebrahim et al (2015) also investigate the same result of correlation for quantitative traits of 20 genotype of barley germplasm. Similar results for grain yield and plant height in barley were reported by other studies (Kisana et al, 1999;Wisal et al, 2109;Arshad et al, 2019). It was observed that the total variation was 81.24% with the Eigen value of 0.99% (Table 3; Figure 1).…”
Section: Correlation Analysissupporting
confidence: 88%